2005
DOI: 10.5713/ajas.2005.1642
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Dietary Biotite V Supplementation as an Alternative Substance to Antibiotics in Growing Pigs

Abstract: This study was conducted to investigate the effects of Biotite V supplementation on growth performance, nutrients digestibility and blood constituents and to evaluate whether Biotite V could replace an antibiotics in growing pigs diet. One hundred twenty pigs with initial body weight of 18.35±0.15 kg were used in a 28 days growth trial. Pigs were allotted to four treatments by sex and body weight in a randomized complete block design. There were six replicate pens per treatment and five pigs per pen. Four diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 16 publications
3
33
0
5
Order By: Relevance
“…It is assumed that clay minerals reduce the speed of feed passage along the intestines, which results in better nutrient conversion and higher water resorption (Castro and Elias, 1978;Papaioannou et al, 2005). Whilst Poulsen and Oksbjerg (1995) did not observe any changes in protein retention using a diet supplemented of with 3% of zeolite, other studies have reported improved digestibility of nutrients (Castro and Elias, 1978;Kyriakis et al, 2002;Chen et al, 2005;Ly et al, 2007), and protein and energy retention (Ly et al, 1996(Ly et al, , 2007Parisini et al, 1999). Some authors put the improvement in protein and energy retention down to the increased activity of pancreatic enzymes due to the supplementation of diets with clay minerals.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…It is assumed that clay minerals reduce the speed of feed passage along the intestines, which results in better nutrient conversion and higher water resorption (Castro and Elias, 1978;Papaioannou et al, 2005). Whilst Poulsen and Oksbjerg (1995) did not observe any changes in protein retention using a diet supplemented of with 3% of zeolite, other studies have reported improved digestibility of nutrients (Castro and Elias, 1978;Kyriakis et al, 2002;Chen et al, 2005;Ly et al, 2007), and protein and energy retention (Ly et al, 1996(Ly et al, , 2007Parisini et al, 1999). Some authors put the improvement in protein and energy retention down to the increased activity of pancreatic enzymes due to the supplementation of diets with clay minerals.…”
Section: Discussionmentioning
confidence: 83%
“…The structure and physical-chemical characteristics of these clay minerals and kaolin, which is a phyllosilicate mineral, are similar . A significant increase in the body weight gain and improved conversion of feed containing clay minerals has been shown by numerous studies (Pond et al, 1981(Pond et al, , 1988Vrzgula et al, 1982;Bartko et al, 1983;Pond and Yen, 1987;Castro and Iglesias, 1989;Cabezas et al, 1991;Papaioannou et al, 2004;Chen et al, 2005;Kolacz et al, 2005;Papaioannou et al, 2005;Alexopoulos et al, 2007;Prvulovic et al, 2007). Naturally, their effect on the efficiency of animals is associated with the type, physicochemical and structural qualities, purity and proportion of these minerals in the diet (Pond and Yen, 1987;Pond et al, 1988;Papaioannou et al, 2004Papaioannou et al, , 2005, and by the age of animals (Papaioannou et al, 2004;Alexopoulos et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last decade, researchers have focused on development of unconventional feed resources. The results of these studies have suggested that supplementation of feed with absorbents leads to improved animal performance (Chen et al, 2005b;Dakovic et al, 2005). It is well known that feeds not only provide nutrients for animals, but also contain a number of contaminants that may enter the food chain via animal products.…”
Section: Introductionmentioning
confidence: 98%
“…However, in 2006, the use of antibiotics as growth promoters was forbidden in the EU (Chen et al 2005) and as an expansion of this policy to other countries can now be expected, intensive research is focused on the development of alternative strategies with the aim to maintain animal health and performance (Chen et al 2005;Bomba et al 2006;Castillo et al 2008). According to Giang et al (2010), piglets fed with probiotic complex diets had higher feed intake, daily gain and better feed conversion after weanling.…”
mentioning
confidence: 99%